Prognostic value of p53 expression in early stage cervical carcinoma treated by surgery - Khunamornpong S. (2014)
Objective: To evaluate the prognostic significance of p53 protein expression in patients with early stage cervical carcinoma treated by surgery alone in a well-controlled study. Methods: A matched case-control study was performed in patients with stage Ib-IIa cervical carcinoma who underwent radical hysterectomy with pelvic lymphadenectomy. Patients had neither lymph node metastasis nor involvement of the parametrium and surgical margins, and did not receive any adjuvant treatment. Cases included 30 patients who had tumor recurrence within 5 years after surgery; controls included 60 patients who were disease-free for at least 5 years after surgery. Cases and controls were within 10 years of age, had the same stage and tumor type, and underwent surgery on as close to the same date as possible. The tumor sizes of cases and controls were within 1 cm of each other. Expression of p53 protein was studied by immunohistochemistry. Expression was considered positive when at least 10% of tumor cells showed nuclear staining. Results: No significant difference of p53 expression was observed between the case group and the control group (33% versus 40%). High histologic grade of tumors and lymphovascular space invasion were significantly associated with tumor recurrence in multivariable analysis (p=0.012 and 0.014, respectively). Conclusion: In this study, expression of p53 did not correlate with tumor recurrence. Immunohistochemistry for p53 protein appears to provide no prognostic information in the patients with early stage cervical cancer treated by surgery.